2011
DOI: 10.1016/j.cub.2010.12.038
|View full text |Cite
|
Sign up to set email alerts
|

A Nonmotor Microtubule Binding Site in Kinesin-5 Is Required for Filament Crosslinking and Sliding

Abstract: Summary Kinesin-5, a widely conserved motor protein required for assembly of the bipolar spindle in vertebrates, forms homotetramers with two pairs of motor domains positioned at opposite ends of a dumbbell shaped molecule [1–3]. It has long been assumed that this configuration of motor domains is the basis of kinesin-5’s ability to drive relative sliding of microtubules [2, 4, 5]. Recently, it was suggested that in addition to the N-terminal motor domain, kinesin-5 also has a non-motor microtubule binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 29 publications
13
100
0
Order By: Relevance
“…KIF11 is built from two homodimers arranged in an antiparallel manner so that identical pairs of heads project from each end of the tetramer, forming a microtubule cross-linker 52,54,55 . The C-terminal tip of the KIF11 tail also contributes to microtubule binding 56 . KIF11 can therefore crosslink the microtubules that project from one centrosome towards the other.…”
Section: Centrosome Separationmentioning
confidence: 99%
“…KIF11 is built from two homodimers arranged in an antiparallel manner so that identical pairs of heads project from each end of the tetramer, forming a microtubule cross-linker 52,54,55 . The C-terminal tip of the KIF11 tail also contributes to microtubule binding 56 . KIF11 can therefore crosslink the microtubules that project from one centrosome towards the other.…”
Section: Centrosome Separationmentioning
confidence: 99%
“…For example, it had been demonstrated for the plus-end tracking Drosophila kinesin-13 KLP10A and KLP59C, that a ring-structure formation required for the plus-end tracking, was favored specifically by the ATP-bound state (Moores et al, 2003;Varga et al, 2006). Finally, it has been recently shown that a non-motor MT binding site in kinesin-5 is required for MT crosslinking (Weinger et al, 2011) and that the tail of Kip3 promotes its accumulation at the MT plus-ends (Su et al, 2011). Therefore, the tail of Kip1 may be involved in plus-end MT tracking, in addition to the role of its motor domain.…”
Section: Plus-end Tracking Activity Of Kip1mentioning
confidence: 99%
“…Eg5 has been shown to exhibit diffusive behavior on microtubules at physiological salt concentration (22,28). To determine whether mammalian Eg5 present in diluted cell extracts showed similar diffusive behavior, we added increasing concentrations of KCl to the motility buffer and examined motor behavior.…”
Section: Tpx2mentioning
confidence: 99%